Pengawasan Penggunaan Tenaga Kerja Asing Di Sumatera Barat - Lerri Pattra (UIR Law Review, 2021)
The Republic of Indonesia was founded, the Indonesian people have realized that work is a human need for citizens. This is stated and mandated in Article 27 paragraph (2) of the 1945 Constitution which states that "Every citizen has the right to work and a living that is decent for humanity". This has implications for the state's obligation to facilitate citizens to obtain decent work for humanity. However, recently the use of foreign workers has become one of the main issues in Indonesia. Foreign workers are foreign nationals holding visas with the intention of working in Indonesian territory. Constitutionally, the use of foreign workers in Indonesia is regulated in Law no. 13/2003 concerning Manpower and strengthened by Law no. 25 of 2007 concerning Investment. Thus the use of foreign workers cannot be avoided because it is constitutionally very possible. Another factor that influences the presence of foreign workers in Indonesia is the agreement of the ASEAN Economic Community (AEC) which began in 2015. This has provided opportunities for the free use of foreign workers for the ASEAN region. What has always been a problem is the high unemployment rate caused by the lack of employment opportunities for Indonesian citizens.